An Early Pliocene North American Deer: Bretzia pseudalces, Its Osteology, Biology, and Place in Cervid History (Bulletin of the Museum of Natural History, University of Oregon, 2015)
The cervid genus Bretzia was first described in 1974 from antler and skull material found in the White Bluffs local fauna of the Pliocene Ringold Formation in south-central Washington. Cervid specimens from the Ringold deposits had been mentioned in published reports in 1917, and 1953, but not until a series of specimens was collected by Willis E. Fry and donated to the Burke Museum in Seattle, about 1970, was the evidence adequate to provide a preliminary diagnosis of Bretzia. The basis of the genus was a series of shed antlers and a portion of the skull of a male individual. Although statements have been made generally characterizing the dentition and postcranial skeleton as similar to Odocoileus, the detailed descriptions of these elements have not previously been published.Bretzia was similar in size to modern O. hemionus (mule deer) but differed in antler morphology and details of the skull, teeth, and postcranial skeleton. The antler pedicles are more widely separated than in most Cervidae. The antlers are distinctive, with a single anterior tine and a posterior beam which in adult individuals forms a large palmate structure. Enough antlers are known to present a developmental series including juvenile, adolescent, adult, and senescent forms. Numerous details of the dentition and postcranial skeleton, including the metacarpals show that Bretzia pseudalces was a telemetacarpal deer (subfamily Capreolinae). The relationship of Bretzia to the living tribes (Alcini, Capreolini, and Rangiferini) is uncertain. Bretzia was one of three known genera (Bretzia, Odocoileus, and Eocoileus) in an early Pliocene (ca. 5 Ma) evolutionary radiation of cervids after the initial immigration from Asia into North America around the time of the Miocene-Pliocene boundary. The Ringold Formation deposits in which the cervid sample was found date to the early Blancan (early Pliocene), probably between 5.0 and 4.8 Ma. The White Bluffs cervid sample largely consists of seasonal (winter and spring) accumulations of bones, antlers, and teeth, which were scattered, weathered, and then buried by spring floods. The proximal environment was a level floodplain with the streams bordered by forest and brush, and surrounded by marsh, small lakes, and grassland. The climate was seasonal but somewhat milder and wetter than at present.